Women`s ski jumping, the 2010 Olympic Games, and the deafening silence of sex segregation, whiteness, and wealth - Travers, A. (Journal of Sport and Social Issues, 2011)
Citing section 15(1) of the Canadian Charter of Rights and Freedoms, 15 women`s ski jumpers took the Vancouver Organizing Committee for the 2010 Olympic and Paralympic Winter Games (VANOC) to court over the exclusion of a women`s ski jumping event. In this analysis of the initial court case and subsequent appeal, I demonstrate that Canadian (and western) citizenship was contested in this legal battle and that gendered, raced, and classed dimensions of citizenship were at play. To make this case, I draw on critical feminist and critical race theorizing on citizenship. From my analysis, three key silences emerge. These concern the underlying assumptions of sex segregation, whiteness, and class privilege.